Implementation of Questionnaire-Based Risk Profiling for Clients in a Workers’ Compensation Environment: An Example in Australian Physiotherapy Practice - Beales, Darren; McManus, L.; Tan, J.; Elliott, C.; Mitchell, T. (Springer, 2019)
Purpose This study investigated the implementation of a risk profiling process for physiotherapy clients with a compensable musculoskeletal problem. Implementation targeted personal (clinician) and external (organisational) factors to facilitate behavioural change with regard to the use of formal, questionnaire-based risk profiling. Methods A theoretical construct was developed for formal questionnaire-based screening to be implemented across 12 private, metropolitan physiotherapy clinics. To target personal (clinician) factors, a multimodal educational procedure was developed focused on use of the ten-item Orebro Musculoskeletal Pain Screening Questionnaire (OMPSQ-10). To target external (organisational) factors, an administrative process was enacted to ensure routine completion of the OMPSQ-10 by compensable clients. Global practice behaviour with regard to the use of formal risk profiling was complete pre- and post-implementation. Results Pre-implementation physiotherapists understood the potential usefulness of formal risk profiling, but the large majority did not routinely have clients complete these types of questionnaires. Post-implementation there was a significant positive shift in behaviour to more frequent use the OMPSQ-10 for new compensable clients. Conclusions The results provide initial support for the use of a framework to develop an implementation strategy to increase physiotherapist adherence to the use of guideline recommended risk profiling questionnaires in clinical practice.